Effect modifiers of lung function and daily air pollutant variability in a panel of schoolchildren. Issue 11 (18th September 2019) - Mentz, Graciela; Robins, Thomas G; Batterman, Stuart; Naidoo, Rajen N
Abstract : Background: Acute pollutant-related lung function changes among children varies across pollutants and lag periods. We examined whether short-term air pollutant fluctuations were related to daily lung function among a panel of children and whether these effects are modified by airway hyperresponsiveness, location and asthma severity. Methods: Students from randomly selected grade 4 classrooms at seven primary schools in Durban, participated, together with asthmatic children from grades 3–6 (n=423). The schools were from high pollutant exposed communities (south) and compared with schools from communities with lower levels of pollution (north), with similar socioeconomic profiles. Interviews, spirometry and methacholine challenge testing were conducted. Bihourly lung function measurements were performed over a 3-week period in four phases. During all schooldays, students blew into their personal digital monitors every 1.5–2 hours. Nitrogen dioxide (NO2 ), nitrogen oxide (NO), sulphur dioxide and particulate matter (<10 μm diameter) (PM10 ) were measured at each school. Generalised estimating equations assessed lag effects, using single-pollutant (single or distributed lags) models. Results: FEV1 declines ranged from 13 to 18 mL per unit increase in IQR for NO and 14–23 mL for NO2 . Among the 5-day average models, a 20 mL and 30 mL greater drop in FEV1 per IQR for NO2 and NO, respectively, among those with airway hyperresponsiveness compared with those without. Effects were seen among those with normal airways. Conclusions: This first panel study in sub-Saharan Africa, showed significant declines in lung function, in response to NO and NO2 with effects modified by airway hyperresponsiveness or persistent asthma.